Factors associated with prescription of modern antidiabetics in newly diagnosed patients with type 2 diabetes. a real-world data study in a Spanish region - Bengoa-Urrengoechea, Irantzu; Aguilar-Palacio, Isabel; Rabanaque, María José; Lallana, María Jesús; Gamba Cabezas, Adriana; Malo, Sara (Frontiers in Pharmacology, 2025)
AimTo describe the patterns of first prescription of antidiabetic drugs (AD) in patients with type 2 diabetes (T2D) and analyze the factors associated with the prescription of a modern one.MethodsObservational longitudinal study conducted in the CArdiovascular Risk factors for HEalth Services research (CARhES) cohort. Individuals older than 15, resident in Aragón (Spain), diagnosed with T2D during 2018–2022 were selected and followed-up until 31st December 2022. Secondary use of data from the health system provided sociodemographic, clinical and pharmacological prescription information. We also considered additional variables by Basic Healthcare Area (BHA) of residence. AD were classified into “classical” and “modern” and their differences were described and compared. A multilevel methodology stratified by sex was developed, considering individual characteristics and characteristics of the BHA of residence, to analyze the factors associated to a modern AD.ResultsOur population-based cohort of 22,892 patients were mostly male, native, low-income and living in non-depopulated BHA. People who were younger, with heart failure, ischemic heart disease, chronic renal failure, obesity, with a previous major adverse cardiovascular event, higher socioeconomic level or lived in less deprived and more depopulated areas were more likely to get a modern AD prescription.ConclusionOur analyses showed that prescribing practices vary according to a range of sociodemographic, clinical and geographical characteristics. Knowledge of these factors is essential for implementing and improving equitable and person-centered approaches.